63ONRG1-fusion-driven solid tumours: A case series indicating the therapeutic potential of afatinib. (24th November 2019) - Goto, Y; Cadranel, J; Weinberg, B A; Duruisseaux, M; Liu, S V; Tolba, K; Branden, E; Doebele, R C; Heining, C; Schlenk, R F; Laskin, J J; Cheema, P K; et al.
Abstract: Background: Neuregulin-1 gene (NRG1) fusions function as oncogenic drivers across various solid tumors, most notably in invasive mucinous adenocarcinoma (IMA) of the lung, and represent a rational potential target for treatment. NRG1 is a growth factor, which binds to ErbB3 or ErbB4 inducing the formation of ErbB3 or 4-containing homo- or heterodimers and activating downstream ErbB-family signaling pathways. Therefore, the ErbB-family blocker afatinib may be a potential treatment option for patients with solid tumors harboring NRG1 fusions. Methods: We report a case series of all known patients with NRG1 fusion-positive solid tumors who were treated with afatinib; afatinib therapy is ongoing for some patients. Results: To date, 18 patients with NRG1 fusion-positive solid tumors have been treated with afatinib (Table). These include 12 cases of non-small cell lung cancer (NSCLC; 7 of which were reported as IMA), 5 cases of gastrointestinal (GI) cancer (primarily pancreatic ductal adenocarcinoma [PDAC]) and 1 case of ovarian cancer. Various NRG1 fusion partners were identified, most commonly CD74 in patients with NSCLC (n = 7; 58%) and ATP1B1 in patients with gastrointestinal cancer (n = 3; 60%). Best response with afatinib among patients with NSCLC was partial response (PR) lasting 24 months (10 months among those specifically with IMA of the lung). Patients with PDAC experienced PR of 3 and 5.5 months' duration, and one patient has an ongoing PR after 7 months. One patient with cholangiocarcinoma had a PR lasting 8 months; another patient with ovarian cancer had stable disease (SD) of unknown duration. Conclusions: Afatinib is a potential treatment option for some patients with solid tumors harboring NRG1 fusions. The efficacy and safety of afatinib will be evaluated in ongoing/planned prospective non-randomized clinical trials of targeted drugs in patients with advanced cancer with potentially actionable genomic variants (NCT02925234 and NCT02693535). Editorial acknowledgement: Greg Plosker of GeoMed, an Ashfield company, part of UDG Healthcare plc. Legal entity responsible for the study: The authors. Funding: Boehringer Ingelheim. Disclosure: Y. Goto: Advisory / Consultancy, Speaker Bureau / Expert testimony: AstraZeneca; Advisory / Consultancy, Speaker Bureau / Expert testimony, Research grant / Funding (self): Eli Lilly; Advisory / Consultancy, Speaker Bureau / Expert testimony: Chugai; Advisory / Consultancy, Speaker Bureau / Expert testimony, Research grant / Funding (self): Taiho Pharmaceutical; Advisory / Consultancy, Speaker Bureau / Expert testimony: Boehringer Ingelheim; Speaker Bureau / Expert testimony, Research grant / Funding (self): Ono Pharmaceutical; Speaker Bureau / Expert testimony, Research grant / Funding (self): Bristol-Myers Squibb; Advisory / Consultancy, Speaker Bureau / Expert testimony, Research grant / Funding (self): Pfizer; Speaker Bureau / Expert testimony: MSD; Speaker Bureau / Expert testimony: Shionogi Pharma; Advisory / Consultancy, Speaker Bureau / Expert testimony, Research grant / Funding (self): Novartis; Advisory / Consultancy: AstraZeneca; Advisory / Consultancy: Glaxo Smith Kline; Research grant / Funding (self): AbbVie; Research grant / Funding (self): Daiichi Sankyo; Research grant / Funding (self): Kyorin. J. Cadranel: Advisory / Consultancy, Research grant / Funding (institution), Non-remunerated activity/ies: AZ; Advisory / Consultancy, Non-remunerated activity/ies: BI; Advisory / Consultancy: MSD; Advisory / Consultancy: BMS; Advisory / Consultancy: Takeda; Advisory / Consultancy, Research grant / Funding (institution): Pfizer; Advisory / Consultancy: Lilly; Advisory / Consultancy, Non-remunerated activity/ies: Roche; Advisory / Consultancy, Research grant / Funding (institution): Novartis. B.A. Weinberg: Speaker Bureau / Expert testimony: Lilly; Speaker Bureau / Expert testimony: Bayer; Research grant / Funding (institution): Novartis; Research grant / Funding (institution): Ipsen; Travel / Accommodation / Expenses: Caris Life Sciences; Travel / Accommodation / Expenses: Boehringer Ingelheim. M. Duruisseaux: Honoraria (self): Roche; Honoraria (self): Takeda; Honoraria (self): Pfizer; Honoraria (self): Novartis; Honoraria (self): AstraZeneca; Honoraria (self): BMS; Honoraria (self): MSD; Honoraria (self): AbbVie; Honoraria (self): Boerhinger ingelheim. S.V. Liu: Advisory / Consultancy: Apollomics; Advisory / Consultancy, Research grant / Funding (institution): AstraZeneca; Advisory / Consultancy: Boehringer Ingelheim; Advisory / Consultancy, Research grant / Funding (institution): Bristol-Myers Squibb; Advisory / Consultancy: Celgene; Advisory / Consultancy: G1 Therapeutics; Advisory / Consultancy, Research grant / Funding (institution): Genentech/Roche; Advisory / Consultancy: Guardant Health; Advisory / Consultancy: Heron; Advisory / Consultancy, Research grant / Funding (institution): Ignyta; Advisory / Consultancy: Inivata; Advisory / Consultancy: Janssen; Advisory / Consultancy, Research grant / Funding (institution): Lilly; Advisory / Consultancy, Research grant / Funding (institution): Merck; Advisory / Consultancy, Research grant / Funding (institution): Pfizer; Advisory / Consultancy: Regeneron; Advisory / Consultancy: Taiho (DSMB); Advisory / Consultancy: Takeda/Ariad; Advisory / Consultancy: Tempus; Research grant / Funding (institution): Bayer; Research grant / Funding (institution): Blueprint; Research grant / Funding (institution): Clovis; Research grant / Funding (institution): Corvus; Research grant / Funding (institution): Esanex; Research grant / Funding (institution): Lycera; Research grant / Funding (institution): Molecular Partners; Research grant / Funding (institution): OncoMed; Research grant / Funding (institution): Rain Therapeutics; Research grant / Funding (institution): Threshold. K. Tolba: Advisory / Consultancy: AstraZeneca; Advisory / Consultancy: Merck; Advisory / Consultancy: Boehringer Ingelheim; Honoraria (self): Foundation One. R.C. Doebele: Advisory / Consultancy, Shareholder / Stockholder / Stock options, Licensing / Royalties, Licenses are licensing fees from patents or biological materials : Rain Therapeutics; Honoraria (self): Guardant; Advisory / Consultancy: Pfizer; Advisory / Consultancy: Trovagene; Advisory / Consultancy, Licensing / Royalties, Licenses are licensing fees from patents or biological materials : Ariad; Advisory / Consultancy: Takeda; Advisory / Consultancy: AstraZeneca; Advisory / Consultancy: Genentech/Roche; Advisory / Consultancy, Research grant / Funding (self), Licenses are licensing fees from patents or biological materials : Ignyta; Advisory / Consultancy, Research grant / Funding (self), Licenses are licensing fees from patents or biological materials: Loxo; Research grant / Funding (self): Mirati; Licensing / Royalties, Licensing fees from patents or biological materials : Abbott Molecular; Licensing / Royalties, Licensing fees from patents or biological materials : GVKbio; Licensing / Royalties, Licensing fees from patents or biological materials: Chugai; Licensing / Royalties, Licensing fees from patents or biological materials : Genentech; Licensing / Royalties, Licensing fees from patents or biological materials: Foundation Medicine; Licensing / Royalties, Licensing fees from patents or biological materials: Black Diamond. R.F. Schlenk: Research grant / Funding (self): Boehringer Ingelheim. J.J. Laskin: Honoraria (self), Research grant / Funding (self): Roche Canada; Honoraria (self): BI Canada; Honoraria (self): AstraZeneca Canada; Research grant / Funding (self): Pfizer Canada. P.K. Cheema: Honoraria (self), Advisory / Consultancy: Astrazeneca; Honoraria (self), Advisory / Consultancy: BI; Honoraria (self), Advisory / Consultancy: BMS; Honoraria (self), Advisory / Consultancy: Novartis; Honoraria (self), Advisory / Consultancy: Takeda; Honoraria (self), Advisory / Consultancy: genomic Health; Honoraria (self), Advisory / Consultancy: Pfizer; Honoraria (self), Advisory / Consultancy: Merck . M.R. Jones: Full / Part-time employment: Qiagen. L.A. Muscarella: Honoraria (self): AstraZeneca; Honoraria (self): Roche; Honoraria (self): Boehringer Ingelheim. A. Cseh: Full / Part-time employment: Boehringer Ingelheim. F. Solca: Full / Part-time employment: Boehringer Ingelheim. D.J. Renouf: Honoraria (self): Celgene; Honoraria (self): Tahio; Honoraria (self): Bayer; Honoraria (self): Ipsen; Honoraria (self): Servier. All other authors have declared no conflicts of interest.